Governance quality and tax morale and compliance in Zimbabwe’s informal sector - Favourate Y. Sebele-Mpofu (Taylor & Francis Group, 2020)
Tax morale was found in literature to shape tax compliance behaviour and to be significantly correlated with strategies of tax effort across countries. In addition views regarding the quality of institutions, the cost-benefit analysis on the use of tax revenues and the quality of governance influence tax morale thus in turn affecting tax compliance. Governance and tax morale are often the most misunderstood and overlooked dimensions of tax compliance yet these are very crucial in the success of tax policy and tax administration. Better tax administration enforcement must be combined with tax reforms that improve transparency and accountability in the use of tax revenues in order to boost tax morale and heighten tax compliance in developing countries, sub-Saharan African countries and Zimbabwe in particular. In these economies corruption in tax administration and government is widespread. The study makes a theoretical contribution to literature on the tax morale, governance quality and tax compliance debate in the informal sector. Three important gaps motivate this study, the lacuna in research that explores the governance-taxation (tax morale and compliance) linkage in developing countries and in Zimbabwe, revenue mobilisation still remains weak in developing countries with fragile capacity to enforce tax compliance thus suggesting an urgent need for research on measures to boost voluntary compliance and lastly taxes are the blood life of any government thus tax compliance is an aspect of major concern.